Audiobook dan Pengetahuan Perawatan Kaki Diabetik pada Pasien Diabetes Mellitus Tipe II - Aulia Septiani Ardiati; Kharisma Pratama; Sutrisno (Jurnal Riset Keperawatan dan Kesehatan, 2026)
Background: Diabetes mellitus is a chronic disease characterized by hyperglycemia that can lead to serious complications such as diabetic foot ulcers, infections, and even amputation. Foot care is essential to prevent these complications. However, many patients with type II diabetes mellitus have not received adequate health education, particularly those with limited reading ability, resulting in poor understanding of diabetic foot care. Audiobooks were selected as an audio-based educational medium because they are easily accessible and do not rely on reading ability. This medium is expected to improve patients’ knowledge of diabetic foot care. Objective: To determine the effect of audiobook use on the level of knowledge of diabetic foot care among patients with type II diabetes mellitus at Kitamura Clinic, Pontianak. Methods: This study employed a quantitative method with a pre-experimental design using a one-group pretest–posttest design. A total of 50 respondents were included using a total sampling technique. The research instrument was the Diabetes Foot Care Knowledge Scale (DFKS) questionnaire. Results: The results of the paired sample t-test showed a p-value of 0.314 (p > 0.05), indicating no statistically significant effect. However, audiobooks demonstrated potential to improve knowledge if delivered repeatedly. Conclusion: The use of audiobooks did not show a statistically significant effect on improving knowledge of diabetic foot care. Nevertheless, audiobooks have the potential to serve as an alternative health education medium when used repeatedly.